Painting on copper: The preparatory layer - Daniel Vega; Isabel Pombo Cardoso; Leslie Carlyle (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In this research about painting on copper technology, 18 historical sources, covering six different languages, dated from the 17th and 18th centuries were collected, allowing to systematise most information about materials and techniques applied on these sorts of paintings. Twelve paintings from the same period mentioned above were studied and compared with the historical literature.